PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA BERBASIS PROJECT BASED LEARNING - Sulastri Kakaly; Jeffrey Payung Langi; Delvia Rimesye Apalem (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
In the condition of there is no development of learning tools applied by lecturers in the lecturing process, resulting in student involvement in learning. The results of the observation of the involvement of 70% of students tend to do visual, listening and writing activities, where students expect information from lecturers, using one-way methods, and effect the students felt bored and less motivated to actively learn. This study aims to (1) obtain information about the characteristics of learning tools developed including Lecturing Plan (RPS) and textbooks; (2) Develop valid learning tools. This research applied development research (Research and development), while the development design uses the 4-D model from Thigajaran. The subject of his research were students of the Ambon State Polytechnic, D-IV Road and Bridge Construction Engineering study program in 2022/2023 Academic Year. Research data collection is carried out through expert validation. The data were further analyzed using descriptive analysis. The results showed that the learning tools developed include RPS, and textbooks were in valid category.